(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Incidence of supraglottic carcinoma is more common which may be related to poor nutrition with personal habit like smoking and chewing habit of betel leaves with various ingredient. Objectives: To find out the incidence, age and sex distribution, occupation and clinical presentation of supraglottic carcinoma of larynx. Materials and Methods: In this prospective study, 30 patients of supraglottic carcinoma are collected from department of ENT and Head-Neck surgery, Combined Military Hospital, Dhaka from July 2012 to July 2013. Results: Patients belongs to different age groups, ranging from 40 to 80 years and maximum patients are in 50 to 60 years of age. The male to female ratio is 5:1. In this series, majority of patients are smoker (66.66%). Most of them are from low socio-economic group. The incidence of lymph node involvement is 40% (12 cases). Maximum number of patients presents with exophytic lesion (60%). Ulcerative lesions are 26.66% and infiltrative lesions are 13.33%. Maximum numbers of patients have T2 lesions (80%). T1 lesions are 20%. In this study all cases are histopathologically confirmed to be squamous cell carcinoma (100%). In this study, all cases are M0 state. Conclusion: Supraglottic carcinoma occurs between 40-80 years of age, more common in 5th and 6th decades. Chewing betel nut and tobacco should be avoided to reduce the risk of supraglottic carcinoma and early presentation & diagnosis will improve the prognosis of patients. JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 224-226